Institutional transformation in Uzbekistan's agricultural and water resources administration: The creation of a new bureaucracy - Resul Yalcin; Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2007)
This paper analyses the institutional transformation of the Uzbek agriculture and water resources administration after Uzbekistan gained independence in 1991. This transformation involved the creation of a joint Ministry of Agriculture and Water Resources in 1997 out of two separate Ministries, and subsequently the process of transforming the region and district based administrative water management system, extended since the creation of the USSR, into an irrigation basin water management system based on the hydrological principles. The latter involved the creation of the Irrigation Basin System Management Authorities in 2003. This study suggests that the merger of the two ministries in 1997 came about as a result of a broader process of organizational change that was part of the post-Soviet state-building process. It was not determined primarily by the idea of achieving equitable water distribution as a normative principle or creating two equally important departments within one ministry, as has been suggested by Wegerich (2005). The analysis of the move towards creating the Irrigation Basin System Management Authorities in 2003 shows that the change should not be seen as a move towards the recreation of a separate Ministry of Water and Ministry of Agriculture. That is, it is not a 'de-merger process' as has, again, been suggested by Wegerich (2005:462). It should rather be seen as a separation of tasks within a single ministry, and a move of the MAWR as a whole to reduce hokims (regional/district governors) influence over its tasks. Overall, the study shows that Uzbekistan's water resources management institutions and organizations are created mainly to serve state-controlled agricultural production. Decisions on water allocation and distribution have always been influenced by the agricultural departments, also when there still was a separate Water Ministry before 1997. Reform processes in the water sector have usually been determined by reforms in agriculture. The theoretical focus of the paper is the analysis of administrative and policy reform process a situation of a 'state-centric' politics (Grindle (1999), in contrast to a 'society-centric' politics. The latter has dominantly been the empirical reference as well as conceptual and instrumental framework of the Western 'policy process' literature. Such frameworks may not be (fully) applicable in evidently state-centric situations like Uzbekistan. The study explores where the initiative for institutional change in the agriculture and water resources domains came from, how new institutional models were generated, how political and economic actors adapt to institutional changes, and, overall how the dynamics of institutional transformation in Uzbekistan is different from that in 'society centric' contexts.
urn:nbn:de:0202-20080911223
Keywords: 350